Older Age, Higher Body Mass Index and Inflammation Increase the Risk for New-Onset Diabetes and Impaired Glucose Tolerance in Patients on Peritoneal Dialysis - Dong, Jie (Perit Dial Int, 2016)
♦ OBJECTIVES: To identify predictors of new-onset diabetes and impaired glucose tolerance (IGT) events in patients undergoing peritoneal dialysis (PD) based on baseline and time-dependent covariates, respectively. ♦ METHODS: In this prospective, single center-based cohort, all non-diabetic incident PD patients between August 2003 and August 2011 were included. All demographic and laboratory data were recorded at baseline. Repeated measurements for laboratory, dialysis prescription, and nutrition parameters were recorded at regular intervals. Multivariable Cox regression models built from baseline and time-dependent variables respectively were used to calculate the hazard ratio (HR) of potential predictors for new-onset diabetes and IGT (NODI). ♦ RESULTS: Of the 612 PD patients, 25 (4.1%) and 7 (1.1%) patients were identified with NODI, respectively, during a mean follow-up period of 32.4 (12.9 – 60.8) months. Using multivariable Cox regression analysis, age and body mass index (BMI) at baseline were significantly associated with NODI after adjustment for potential confounders. During follow-up, time-dependent BMI and serum high-sensitive C-reactive protein (HS-CRP) independently predicted the risk for NODI. Patients with NODI had significantly elevated plasma glucose concentrations and BMI from the start of PD therapy, with serum HS-CRP maintained at high levels. Dietary/dialysate energy intake and other laboratory parameters were not correlated with NODI risk either as baseline or time-dependent variables. ♦ CONCLUSIONS: Traditional and uremic-related risk factors, such as older age, higher BMI, and inflammation, contribute to new-onset diabetes and impaired glucose tolerance in PD patients.